Source Analysis as a Necessary Condition for Preparing an Edition’s Text (on the Material of the New Testament Prepared by the Editorial Circle of Epiphany Slavinetsky and Evfimi Chudovsky, Second Half of the 17th Century) - Pentkovskaya, Tatiana V. (Slavistica Vilnensis, 2019)
The Church Slavonic New Testament of the second half of the 17th century, translated under the leadership of Epiphanius Slavinetsky and Euthymius of Chudov Monastery, belongs to the translations made from several originals in different languages. The main source of the translation includes additional texts derived mainly from Polish sources. Their study is important for the reconstruction of the general idea of the translators and of the type of edition prepared by them.
Keywords: New Testament translations of the second half of the 17th century; Greek-Church Slavonic bilingualism; source analysis; linguistic edition